Debureaucratization of child welfare services in three free communes: A case-based analysis and discussion - Jensen, Hanne Louise Søgaard; Strandby, Martin Williams (Politica, 2022)
This article analyzes and discusses a case of successful debureaucratization; the free-commune experiments regarding child welfare services from 2017-2020 where three Danish municipalities were allowed to replace key provisions in the social laws stipulating how to perform social work and administer social cases, with newly developed forms of social work. The analysis starts from the trifecta of rule exemptions, employee motivation and managerial focus, and shows – based on repeated survey data and qualitative interviews – how each of the three has materialized in this “debureaucratization success”. Furthermore, we discuss the relation between the three components. We argue that rule exemptions are significant as a launch-pad for changing how social work is done locally, via unleashing managerial focus and employee motivation. Rule exemptions appear almost redundant, since the largest debureaucratizing changes happen via the initiated change processes, where managerial focus appears to play a decisive role.